The effect of temperature, cooking time, and salt concentration on the thiocyanate content of cabbage (Brassica capitata L.). - Sagun, G. G. (Compendium of Human Ecology Researches in the Philippines, 2003)
The presence of glucosinolates in Brassicas is reported to be responsible for the anticarcinogenic properties of these vegetables. The breakdown of glucosinolates into thiocyanate ions and indole acetonitriles makes possible the estimation of the amount of glucosinolates in Brassicas. The effect of processing conditions such as temperature, cooking time, and presence of salt were determined using colorimetric assay. Results showed that thiocyanate content decreased as temperature is increased. Lowest thiocyanate content was observed at 75 °C of 0.28mg per 100g sample. A significant increased in thiocyanate content was observed as the temperature reached boiling point (0.36mg/100g). Generally, increased temperature prolonged cooking time coupled with salt decreased the overall thiocyanate content of cooked cabbage thereby decreasing its anticarcinogenic property.